Definition of the Rectum: An International, Expert-based Delphi Consensus. Issue 6 (December 2019) - D'Souza, Nigel; de Neree tot Babberich, Michael P. M.; d'Hoore, Andre; Tiret, Emmanuel; Xynos, Evaghelos; Beets-Tan, Regina G. H.; Nagtegaal, Iris D.; Blomqvist, Lennart; Holm, Torbjorn; Glimelius, Bengt; Lacy, Antonio; Cervantes, Andres; et al.
Abstract : Background: The wide global variation in the definition of the rectum has led to significant inconsistencies in trial recruitment, clinical management, and outcomes. Surgical technique and use of preoperative treatment for a cancer of the rectum and sigmoid colon are radically different and dependent on the local definitions employed by the clinical team. A consensus definition of the rectum is needed to standardise treatment. Methods: The consensus was conducted using the Delphi technique with multidisciplinary colorectal experts from October, 2017 to April, 2018. Results: Eleven different definitions for the rectum were used by participants in the consensus. Magnetic resonance imaging (MRI) was the most frequent modality used to define the rectum (67%), and the preferred modality for 72% of participants. The most agreed consensus landmark (56%) was "the sigmoid take-off, " an anatomic, image-based definition of the junction of the mesorectum and mesocolon. In the second round, 81% of participants agreed that the sigmoid take-off as seen on computed tomography or MRI achieved consensus, and that it could be implemented in their institution. Also, 87% were satisfied with the sigmoid take-off as the consensus landmark. Conclusion: An international consensus definition for the rectum is the point of the sigmoid take-off as visualized on imaging. The sigmoid take-off can be identified as the mesocolon elongates as the ventral and horizontal course of the sigmoid on axial and sagittal views respectively on cross-sectional imaging. Routine application of this landmark during multidisciplinary team discussion for all patients will enable greater consistency in tumour localisation. Abstract : Supplemental Digital Content is available in the text